Efecto agronómico y rendimiento de cultivares de arroz (Oryza sativa L.), a las aplicaciones de complejos hormonales - Cano Maquilón, Francisco Javier (2019)
This experimental work was established on the grounds of the “Cacharí” Project, belonging to Ing. Daniel Cano Herrera, 4.5 km from the Faculty of Agricultural Sciences of the Technical University of Babahoyo. The soil has a flat topography, loamy-clayey texture and regular drainage. It was used as planting material, rice seeds SFL-11 and INIAP 16. The treatments were constituted after the interaction of rice varieties with the hormonal complex Dyna forte in doses of 0.5; 1.0 and 1.5 L / ha; Cytokin in doses of 0.5 L / ha plus an absolute control. The experimental design called "Randomized complete blocks" was used, in factorial arrangement A x B, with ten treatments and three repetitions, where Factor A was the varieties and Factor B the doses of hormonal complex. All the variables evaluated were subjected to the analysis of variance and to determine the statistical difference the Tukey test was used. During the development of the crop, the following agricultural work and practices were carried out such as land preparation, planting, irrigation, fertilization, weed control and phytosanitary and harvest. From the results obtained, it was determined that the use of the hormonal complex caused positive effects on the development and yield of the rice crop, in the varieties SFL-11 and INIAP-16; the SFL-11 variety without the application of hormonal products flourished in less time; the planting of the INIAP-16 variety by applying Dyna forte at a dose of 1.0 L / ha influenced for a greater plant height, number of tillers and panicles / m2, panicle length, grains per panicle and weight of 1000 grains and the highest grain yield with 7255.0 kg / ha and greater net profit with $ 910.65 was presented in the planting of the INIAP-16 variety using Dyna forte in doses of 1.0 L / ha